2016
DOI: 10.21608/jppp.2016.52474
|View full text |Cite
|
Sign up to set email alerts
|

Screening Potential of Some Bacterial Species and Trichoderma hrzianum Against Sclerotinia sclerotiorum on Cucumber.

Abstract: Eight bacterial isolates belonged to 4 genera, i.e., Serratia sp.,(one isolate) Bacillus subtilis, (three isolates) Bacillus thuringiensis,(two isolates) Streptomyces sp.(one isolate) and Pseudumonas flourescens(one isolate) and one fungal isolate (T. harzianum) were isolated from cucumber rhizosphere to evaluate their potential as antagonists to Sclerotinia stem and root rot on cucumber. In vitro, all isolates resulted in a significant reduction in hyphal growth of pathogenic fungus, Streptomyces sp. was more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…The inhibitory effect of Pseudomonas spp. AFP104 isolate on mycelial growth of S. sclerotiorum was reported as 83.3% by Soylu et al (2005), while the inhibition ratio of pathogenic fungus by Streptomyces sp., Pseudomonas fluorescens and Bacillus subtilis (Bs1) bacteria was 72.2, 68.0, 62.22%, respectively (Helmy, 2016). El-Tarabily et al (2000) reported the inhibitory effect of Serratia marcescens, Streptomyces viridodiasticus and Micromonospora carbonacea, on the growth of S. minor in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of Pseudomonas spp. AFP104 isolate on mycelial growth of S. sclerotiorum was reported as 83.3% by Soylu et al (2005), while the inhibition ratio of pathogenic fungus by Streptomyces sp., Pseudomonas fluorescens and Bacillus subtilis (Bs1) bacteria was 72.2, 68.0, 62.22%, respectively (Helmy, 2016). El-Tarabily et al (2000) reported the inhibitory effect of Serratia marcescens, Streptomyces viridodiasticus and Micromonospora carbonacea, on the growth of S. minor in vitro.…”
Section: Discussionmentioning
confidence: 99%